English Day Program and Its Impact on Students' Speaking Proficiency A Socio-linguistic Exploration - Ramadani, Lilian; Dharmawan, Yanuarius Yanu (Edupedia Publisher, 2025)
This study explores the sociolinguistic dimensions of the English Day program and its impact on students' speaking proficiency at SMA Global Madani. By examining how language practices like English Day influence students' confidence, fluency, and language identity, this research highlights the importance of authentic communication environments in language learning. The study employed qualitative methods, including observations and interviews with 15 purposively selected students. The findings indicate that while the English Day program significantly improved students' speaking proficiency, it also presented sociolinguistic challenges such as anxiety and self-consciousness. Nonetheless, consistent exposure to English and supportive social environments helped foster students' confidence and communicative skills. This study emphasizes the importance of contextual and sociolinguistic factors in shaping effective language acquisition practices.